Lizard - Yoshimoto, Banana 1964- (Grove Press, 1995)
Six short stories by a Japanese woman writer known for her unusual themes. In Blood and Water, a woman abandons the religious commune where she was raised, goes to the big city and finds another idol of worship, a charismatic lover. The story looks at the connection between spiritual and romantic fervor. By the author of Kitchen.
Keywords: Japan -- Fiction; Short stories